An equivalent circuit model for wide‐band analysis of defected ground structures with asymmetric slot and multiple slots. Issue 1 (27th August 2020) - Van Nechel, Evi; Ferranti, Francesco; Rolain, Yves; Lataire, John
Abstract: In this article, we propose a novel equivalent circuit model that can accurately represent the wide‐band behavior of a defected ground structure with a slot that is positioned asymmetrically with respect to the signal transmission line and also with multiple slots. The inclusion of losses is crucial to guarantee a high level of accuracy. The number of circuit elements is very parsimonious, which makes the model efficient and the identification of the equivalent circuit parameters simple. Pertinent measurement and simulation results validate the proposed model in different cases.